Off‐Hour Admission and Mortality Risk for 28 Specific Diseases: A Systematic Review and Meta‐Analysis of 251 Cohorts. Issue 3 (18th March 2016) - Zhou, Yanfeng; Li, Wenzhen; Herath, Chulani; Xia, Jiahong; Hu, Bo; Song, Fujian; Cao, Shiyi; Lu, Zuxun
Abstract : Background: A considerable amount of studies have examined the relationship between off‐hours (weekends and nights) admission and mortality risk for various diseases, but the results remain equivocal. Methods and Results: Through a search of EMBASE, PUBMED, Web of Science, and Cochrane Database of Systematic Reviews, we identified cohort studies that evaluated the association between off‐hour admission and mortality risk for disease. In a random effects meta‐analysis of 140 identified articles (251 cohorts), off‐hour admission was strongly associated with increased mortality for aortic aneurysm (odds ratio, 1.52; 95% CI, 1.30–1.77), breast cancer (1.50, 1.21–1.86), leukemia (1.45, 1.17–1.79), respiratory neoplasm (1.32, 1.20–1.26), pancreatic cancer (1.32, 1.12–1.56), malignant neoplasm of genitourinary organs (1.27, 1.08–1.49), colorectal cancer (1.26, 1.07–1.49), pulmonary embolism (1.20, 1.13–1.28), arrhythmia and cardiac arrest (1.19, 1.09–1.29), and lymphoma (1.19, 1.06–1.34). Weaker (odds ratio <1.19) but statistically significant association was noted for renal failure, traumatic brain injury, heart failure, intracerebral hemorrhage, subarachnoid hemorrhage, stroke, gastrointestinal bleeding, myocardial infarction, chronic obstructive pulmonary disease, and bloodstream infections. No association was found for hip fracture, pneumonia, intestinal obstruction, aspiration pneumonia, peptic ulcer, trauma, diverticulitis, and neonatal mortality. Overall, off‐hour admission was associated with increased mortality for 28 diseases combined (odds ratio, 1.11; 95% CI, 1.10–1.13). Conclusions: Off‐hour admission is associated with increased mortality risk, and the associations varied substantially for different diseases. Specialists, nurses, as well as hospital administrators and health policymakers can take these findings into consideration to improve the quality and continuity of medical services.